Metal ion-induced separation of valuable organic acids from a depolymerized mixture of lignite without using organic solvents. Issue 6 (21st January 2020) - Hao, Jianxiu; Han, Limin; Yang, Keli; Zhao, Hongye; Li, Xiaomin; Ban, Yanpeng; Li, Na; Zhou, Huacong; Liu, Quansheng
Abstract : Metal ion-induced separation of valuable organic acids from complex lignite depolymerized mixtures was proposed and proved to be an efficient, green, and facile separation process with easily tunable separation selectivity. Abstract : Due to the low utilization efficiency of lignite as a primary energy source, the valuable and clean use of lignite becomes important. Oxidative depolymerization of lignite into valuable organic acids (VOAs) has been identified to be feasible, but the difficulty in separating VOAs from the complex lignite depolymerized mixture (LDM) limits the potential application of this route. In this study, based on the coordination interactions between metal ions and carboxylate groups in VOAs, the metal ion-induced separation of VOAs from the LDM was proposed. The results proved that most of the studied metal ions (M n + ) could selectively form M–VOA precipitates with the VOAs in LDM and transferred the VOAs from the water phase into the solid precipitates. Then, the intermediate M–VOAs could be dissolved in diluted NaOH solution to release the VOAs, with M n + being transformed into M(OH) n . The separation yield and selectivity could be tuned facilely by various metal ions at different dosages, pH, and temperatures. The process could be fulfilled under near-room temperature in water without the use of organic solvents. Due to its efficiency, tunable selectivity, and green nature, the proposed separation strategy may find potential applications in the valuable and clean use of lignite sources.